THE EFFECT OF GLYCEROL PLASTICIZER IN THE PRODUCTION OF CELLULOSE-BASED BIOPLASTIC FROM DURIAN RIND - Benaldo Adikara, Andrew
Plastic is the most commonly used packaging material in the food and beverage industry due to its affordability and durability. However, the long degradation time of plastic leads to the accumulation of plastic waste, which can potentially harm the environment. One solution is the production of bioplastics, which can be decomposed by microorganisms and are made from renewable materials. Bioplastics can be made from biomass materials such as cellulose, starch, pectin, and lignin. Cellulose is the most abundant renewable polymer in nature and is used as a raw material due to its renewability, low cost, non-toxicity, biocompatibility, biodegradability, and chemical stability. This study aims to investigate the effect of glycerol as a plasticizer in the production of biodegradable cellulose-based plastic packaging derived from durian peel. The experiment variations are the amounts of glycerol added to the bioplastic, which are 100 ?L, 500 ?L, and 1000 ?L. The physical characteristics of the packaging are tested, including color measurement, tensile strength measurement, permeability and liquid absorbency measurement, Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR) testing, and biodegradability testing. Sample IDs for each glycerol composition variation are G100, G500, and G1000. The cellulose yield from the durian peel isolation is 7.11% with a cellulose purity of 70.2%. The isolate also contains extractives, hemicellulose, and lignin components at 12.3%, 16.3%, and 1.13%, respectively. FTIR testing of the bioplastic confirms the presence of glycerol and cellulose. The addition of glycerol results in more significant bioplastic decomposition at lower temperatures. SEM analysis shows that as the glycerol concentration increases, the fibers become more spaced out, followed by a less fibrous surface appearance of the bioplastic, making it more flexible and stretchable, resembling plastic properties. The permeability and absorbency of the bioplastic to water increase with higher glycerol content. Consequently, the degradation rate of the bioplastic samples increases with higher glycerol content. Food packaging using bioplastic samples can prevent mold growth on the tested food; however, this may be due to low moisture content, followed by an increase in hardness value in the samples.